MiR-363-3p induces tamoxifen resistance in breast cancer cells through PTEN modulation - Yaning Liang; Cuiyu Shi; Yu Wang; Bingjie Fan; Wei Song; Rong Shen (Scientific Reports)
Abstract Nowadays, the investigation for overcoming tamoxifen (TAM) resistance is confronting a considerable challenge. Therefore, immediate attention is required to elucidate the mechanism underlying TAM resistance in breast cancer. This research primarily aimed to define how miRNA-363-3p facilitates resistance to TAM in breast cancer. High-throughput miRNA sequencing was performed using RNAs prepared from breast cancer MCF-7 cells and TAM-resistant MCF-7 cells (MCF-7-TAM). An increase in miRNA-363-3p levels was observed in MCF-7-TAM cells. In MCF-7 cells, miRNA-363-3p directly targeted and negatively regulated phosphatase and tensin homolog (PTEN). Reduction of miRNA-363-3p retarded cell growth and accelerated cell apoptosis, thereby enhancing the sensitivity of TAM. Moreover, analysis using the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway showed significant enrichment of target genes within the phosphoinositide-3-kinase (PI3K)/protein kinase B (AKT) signaling pathway. Ultimately, miR-363-3p decreased the responsiveness of breast cancer cells to TAM by targeting and suppressing PTEN through a mechanism associated with the PI3K-Akt pathway. Therefore, these results suggest that miR-363-3p-dependent PTEN expression contributes to the mechanisms underlying breast cancer endocrine resistance.